2010
DOI: 10.1124/jpet.110.173740
|View full text |Cite
|
Sign up to set email alerts
|

A Substituted Anilino Enaminone Acts as a Novel Positive Allosteric Modulator of GABAA Receptors in the Mouse Brain

Abstract: A small library of anilino enaminones was analyzed for potential anticonvulsant agents. We examined the effects of three anilino enaminones on neuronal activity of output neurons, mitral cells (MC), in an olfactory bulb brain slice preparation using wholecell patch-clamp recording. These compounds are known to be effective in attenuating pentylenetetrazol-induced convulsions. Among the three compounds tested, 5-methyl-3-(4-trifluoromethoxy-phenylamino)-cyclohex-2-enone (KRS-5Me-4-OCF 3 ) showed potent inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…Data from our electrophysiology studies revealed that the lead analog KRS−5Me−4−OCF 3 (1) showed activity as a positive allosteric modulator of GABA at the GABA A benzodiazepine receptor site [8]. Using lead-based drug design methods, we proposed that optimizing the KRS−5Me−4−OCF 3 analog with an amide bridge functionality between the enaminone intermediate and the aromatic ring while maintaining the fluorinated group on the benzene ring (as seen in Figure 2) will allow for the analogs to retain anticonvulsant activity with better efficacy and little to no neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Data from our electrophysiology studies revealed that the lead analog KRS−5Me−4−OCF 3 (1) showed activity as a positive allosteric modulator of GABA at the GABA A benzodiazepine receptor site [8]. Using lead-based drug design methods, we proposed that optimizing the KRS−5Me−4−OCF 3 analog with an amide bridge functionality between the enaminone intermediate and the aromatic ring while maintaining the fluorinated group on the benzene ring (as seen in Figure 2) will allow for the analogs to retain anticonvulsant activity with better efficacy and little to no neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Our hypothesis is that the substituted site in enaminones contributes to the mode of action of these compounds. Recent work determined the mechanism of anticonvulsant action of three enaminone compounds that have non- ortho -substituted cyclohexenone [ 18 ]. Specifically, the effects of three anilino enaminones on neuronal activity of output neurons, mitral cells, in an olfactory bulb brain slice preparation using whole-cell patch-clamp recording has been examined.…”
Section: Enaminones In Drug Discovery and Developmentmentioning
confidence: 99%
“…E139 is a para -bromo anilino enaminone derivative with a methyl ester substituted moiety at cyclohexenone and Compound 30 is the benzylamino analog. From [ 18 ].…”
Section: Synthesis Of Anilino Enaminonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Enaminones have also played an important role as building blocks for generating libraries of novel drug candidates (12)(13)(14)(15)(16). More recently, the therapeutic potential of the enaminone building block itself has become an active area of investigation (9,(17)(18)(19)(20).…”
mentioning
confidence: 99%